Propuesta de sostenibilidad para la utilización de energía fotovoltaica en zonas residenciales de Bogotá. Un estudio de caso para el Conjunto Residencial Ciudad Tintal 2 Etapa 2. (2022)
Throughout the document a sustainability proposal was generated for the use of photovoltaic energy in the residential area Ciudad Tintal 2 Stage 2, belonging to the town of Kennedy in Bogotá. This study aims to highlight the opportunities presented by the residential complex related to the generation of clean energies, preserving their care, optimizing the resources of the electrical matrix proposing to minimize the cost of the final consumer by studying the guidelines for implementing an alternative energy system in this space. Key points of electricity consumption will be identified to prioritize and determine the amount of energy to be supplied (VA/h = w/h) in the common area of the property. Once these aspects have been determined, a market price study will be carried out to estimate the value of the investment in the photovoltaic system that will guarantee the satisfaction of the need taking into account the constraints of the unit. Finally, a proposal is proposed that contemplates temporary economic compensation in which the investor will recover his efforts, the cost-benefit ratio and all the technical, environmental and economic benefits.